Feeding strategies for improving ruminant productivity in the post-COVID 19 pandemic era particularly for small holders - Dennis P. Poppi; Kusmartono Kusmartono; Kasmyati Kasmyati; Simon P Quigley; Karen J Harper (Jurnal Ilmu-Ilmu Peternakan (Indonesian Journal of Animal Science), 2021)
COVID-19 has highlighted the need for robust cattle supply chains using local feed resources. Higher Income Over Food Costs (IOFC) are usually achieved when live weight gains are high and the cost of the ingredients are low. There is a need to formulate rations with high metabolisable energy (ME) and crude protein (CP) to achieve the high live weight gain. Rations can be formulated locally by farmer co-operatives, entrepreneurs and local commercial enterprises to take advantage of cheaper prices for local ingredients. To do this, rations need to be altered quickly to take advantage of local fluctuations in prices and availability of ingredients. A recent ACIAR funded project has developed a least cost ration (ACIAR LCR) system to formulate rations to meet minimum ME and CP contents for beef cattle using locally available ingredients. The use of cassava and its various products in combination with protein sources, such as tree legumes and high protein by-products, have markedly improved IOFC.